Bariatric Surgery: Consequences on Functional Capacities in Patients With Obesity - Reinmann, Aline; Gafner, Simone Chantal; Hilfiker, Roger; Bruyneel, Anne-Violette; Pataky, Zoltan; Allet, Lara (Frontiers in Endocrinology, 2021)
Introduction: Bariatric surgery leads to loss of fat and fat-free mass (FFM). To preserve FFM it is recommended that weight loss interventions are accompanied by physical activity. However, it remains unknown if functional capacities spontaneously improve after a substantial weight loss. Study’s aim was to assess the effect of bariatric surgery on strength, functional capacities and quality of life of participants with a body mass index (BMI) ≥ 35 kg/m2. Method: Anthropometric parameters (weight, BMI, waist circumference), physical functions (quadriceps strength, walking capacity, spatio-temporal gait parameters, dynamic balance, lower limb power) and quality of life were assessed before and at three months after the bariatric surgery in 33 individuals who did not follow any physical activity program. Results: The anthropometric parameters, quality of life and three functional abilities (walking capacity, normal gait speed and lower limb power) improved significantly three months post-surgery. In contrast, fast gait speed, absolute strength, normalized strength, and dynamic balance did not improve. Discussion: A massive weight loss should be accompanied by an exercise program aiming to maintain FFM and to enhance muscle strength and balance. Such a program might also enhance functional capacities and help to sustain the weight loss over time.